The Role of Semantic Priming in Relative Clause Attachment Ambiguity Resolution in Persian - Eskandar Samadi; Mohammad nabi karimi; Esmat Babaii (Journal of Language Horizons, 2022)
The present study investigated the role of semantic priming in the processing of ambiguous sentences containing Relative Clauses (RCs) preceded by a complex Noun Phrase (NP) by Persian native speakers. To this end, in a self-paced reading task using E-prime software, 63 Persian native speakers read sentences containing ambiguous RCs in their L1, i.e. Persian. The type of semantic relationship in this study was the one between the RC and one of the NPs within the complex NP to find out whether priming one of the NPs through this semantic manipulation would affect Persian native speakers’ attachment preferences. The results of the off-line post interpretive (RC attachment preferences) and on-line data (reading times) revealed that semantic priming affects participants’ attachment preferences, which suggests that their parsing preferences are not guided purely by syntactic information. The findings are in line with constraint-based models of sentence parsing, which assume that, during parsing, multiple sources of information interact and each of them constrains the interpretation in a particular way. The results also support the predictions of the Spreading Activation Model and Lexical Priming Theory.